Impact of breastfeeding interventions among United States minority women on breastfeeding outcomes: a systematic review - Sofia Segura-Pérez; Amber Hromi-Fiedler; Misikir Adnew; Kate Nyhan; Rafael Pérez-Escamilla (BMC, 2021)
Abstract Background In the U.S., strong ethnic/racial, socioeconomic, demographic, and geographic breastfeeding (BF) inequities persist, and African American and Hispanic women are less likely to meet their breastfeeding goals compared to White women. This systematic review (SR) was designed to answer the question: What is the impact of breastfeeding interventions targeting ethnic/racial minority women in the U.S. on improving BF initiation, duration and exclusivity rates? Methods The SR was conducted following the Institute of Medicine Guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. The study protocol was developed and registered a priori in PROSPERO (ID#CRD42020177764). The electronical databases searched was MEDLINE All (Ovid). Search strategies were led by the team's expert public health librarian using both controlled vocabulary and free text queries and were tested against a validated set of relevant papers included in existing reviews. The GRADE methodology was used to assess the quality of the studies. Results We included 60 studies that had randomized (n = 25), observational (n = 24), quasi-experimental (n = 9), or cross-sectional (n = 2) designs. The studies focused on populations that were multi-ethnic/racial (n = 22), only Hispanic (n = 24), only Black (n = 13), and only American Indian (n = 1). The study interventions were classified following the socioecological model: macrosystem/policy level (n = 6); community level (n=51), which included healthcare organizations (n = 34), The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) (n = 9), and community organizations/public health institutions (n = 8); and  interpersonal level (n = 3). Conclusions Policy and community level interventions delivered through WIC, healthcare facilities, and community agencies) are likely to improve BF outcomes among women of color. The combination of interventions at different levels of the socioecological model has not been studied among minority women in the U.S. Implementation science research is needed to learn how best to scale up and sustain effective BF interventions, taking into account the needs and wants of minority women. Thus, it is strongly recommended  to conduct large scale implementation research studies addressesing how to strengthen the different health and social environments surrounding women of color in the U.S. to improving their BF outcomes.